Una rilettura del caso del piccolo Hans - Candusso, Sandro (Metapsychologica - rivista di psicanalisi freudiana, 2023)
This article reconstructs the clinical history of Little Hans and sheds light on the flaws in the standard reading of the case, in order to gain a deeper understanding of the identifications and symbolism that appear in it. In particular, emphasis is placed on the scientific approach with which Hans seeks the truth about the issues that torment him the most, albeit the obstacles he bumps into along the way. His line of action strikingly resembles the way scientific knowledge is actually produced, to a point that the image of Hans as a young scientist looks like something more than a simple analogy.